Hydrothermal alteration, lithogeochemical marker units and vectors towards mineralisation at the Svärdsjö Zn-Pb-Cu deposit, Bergslagen, Sweden - Fahlvik, Anton; Kampmann, Tobias Christoph; Jansson, Nils F. (GFF, 2022)
The Svärdsjö Zn-Pb-Cu deposit is situated in the heavily mineralised Bergslagen lithotectonic unit of the Fennoscandian shield, south-central Sweden. Intense hydrothermal alteration followed by a strong overprint by deformation and metamorphism during the Svecokarelian orogeny complicate interpretation of the local geology. Integration of whole-rock lithogeochemical and petrographic methods has allowed the mainly dacitic volcanic host succession and effects of ore-related hydrothermal alteration to be characterised. Mineralisation is hosted by 2–15 m thick, commonly skarn-altered dolomitic marble interbeds. Zones of strong–intense hydrothermal chlorite-sericite alteration envelop the marble units, recording mass gains of Fe and Mg, as well as Na depletion. Minerals such as cordierite, anthophyllite and sillimanite formed in these rocks during regional metamorphism. Mineralisation via sub-seafloor replacement is suggested for the deposit based on alteration zoning and the irregular, stratabound, marble-hosted style of sulphide lenses. It is inferred that mineralisation formed via neutralisation of hot, acidic metalliferous fluids. Geochemically and lithologically distinct units adjacent to the mineralised zones can serve as marker units to aid further exploration in the area. Mass change calculations reveal that Fe and Mg enrichment, as well as Na depletion exhibit detectable changes extending up to 100 m from the mineralised lenses, providing exploration vectors. Validerad;2023;Nivå 2;2023-12-05 (hanlid); Funder: Boliden Mineral AB; Full text license: CC BY-NC-ND